Medicinal Use of Chicory (Cichorium intybus L.) - Łukasz Duda; Karol Kamil Kłosiński; Grażyna Budryn; Andrzej Jaśkiewicz; Damian Kołat; Żaneta Kałuzińska-Kołat; Zbigniew Włodzimierz Pasieka (MDPI AG, 2024)
The aim of this review is to discuss the numerous health-promoting properties of Cichorium intybus L. and bring together a range of publications to broaden knowledge and encourage further research and consideration of the plant use as treatment for a range of conditions. A comprehensive search of articles in Polish and English from 1986-2022 years was carried out in PubMed, Google Scholar and ScienceDirect using the keywords chicory, Cichorium intybus L., sesquiterpene lactones and their synonyms. Articles were checked for titles, abstracts, and full-text reviews. The first part of the review article discusses chicory, the countries in which it is found, its life cycle or modern cultivation methods, as well as its many uses, which will be discussed in more detail later in the article. The increased interest in plants as medicines or supplements is also briefly mentioned, as well as some limits that are associated with the medical use of plants. In the Results and Discussion section, there is a discussion of the numerous health-promoting properties of Cichorium intybus L. as a whole plant, with its collection of all the components, and we then examine the structure and the individual constituents of Cichorium intybus L. Among these, this article discusses those that can be utilized for causal applications in medicine, including sesquiterpene lactones and polyphenols, mainly known for their anti-cancer properties, although, in this article, their other health-promoting properties are also discussed. The article also examines inulin, a major component of Cichorium intybus L. The Discussion and the Conclusions sections propose directions for more detailed research and the range of factors that may affect specific results, which may have safety implications when used as supplements or medications.